THE SYNCHRONOUS AND ASYNCHRONOUS LEARNING AT ENGLISH DEPARTMENT OF UNIVERSITIES IN SOUTH KALIMANTAN: PRACTICES AND CHALLENGES - Hizriani, Nani; Nor, Hidayah; Saadillah, Saadillah (University of Kuningan, 2022)
The purposes of this research are to describe types, practices of Synchronous and Asynchronous learning and to explore the challenges faced by the lecturers at English Departments in South Kalimantan. The researchers employed mixed-methods sequential explanatory design which consist of two distinct phases, quantitative (numeric data) by using questionnaire followed by qualitative by using observation and interview in order to elaborate the results obtained from quantitative data. This research was undertaken in nine English Departments in South Kalimantan. The participants were 53 English lecturers who teach at those universities. The types of synchronous used by the lecturers were Text-based chat / Instant Messaging / Online Chat (WhatsApp), Web Conferencing / Virtual Classroom (Zoom and Google Meet), Whiteboards, Real-time and Non real time document sharing (Google documents). The asynchronous types were Email, WhatsApp Group, Google Classroom, YouTube Link, PDF Files, MS Words Files, Learning Management System (LMS)/e-learning. The lecturers used direct feedback, real time classroom interaction and communication during synchronous learning. On the other hand, they provided delayed feedback, practiced not real time classroom interaction and communication in asynchronous learning. They facilitated individual and group collaboration for both learnings. The lecturers faced a number of challenges in implementing Synchronous and Asynchronous learning such as Technological Problems / Internet Connection, Students’ Motivation, Classroom Management, Lack of technological supports, Students’ Participation, Interaction, Time Management, Feedback, Materials Development, Monitoring, Instructional Method, Flexibility, and Cost Effectiveness.